Pengaruh Kompensasi Dan Motivasi Terhadap Kepuasan Kerja Pegawai Kantor Dinas Pariwisata Dan Kebudayaan Kabupaten Kolaka Timur - Asta Hidayanti; Fitri Kumalasari; Suwarto Suwarto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to determine: 1) The influence of compensation on job satisfaction of employees at the East Kolaka Regency Tourism and Culture Office. (2) The Influence of Motivation on Job Satisfaction of Employees at the East Kolaka Regency Tourism and Culture Office. This research uses a quantitative method approach. Data collection in this research used observation studies, documentation and questionnaires. The population of this research is all employees who work at the East Kolaka Regency Tourism and Culture Office. Meanwhile, the sample for this research was 34 people, with the sample determined using census techniques. Research instrument testing uses validity and reliability tests with SPSS 25.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 4.0. Based on the research results, it is known that the Compensation Variable has a positive and significant effect on Employee Job Satisfaction, which is shown by a P-Values ​​value of 0.020. And the Motivation Variable has a positive and significant effect on Employee Job Satisfaction, this is shown by a P-Values ​​value of 0.000.